2022
DOI: 10.3389/fmicb.2022.852571
|View full text |Cite
|
Sign up to set email alerts
|

The Verticillium dahliae Spt-Ada-Gcn5 Acetyltransferase Complex Subunit Ada1 Is Essential for Conidia and Microsclerotia Production and Contributes to Virulence

Abstract: Verticillium dahliae is a destructive soil-borne pathogen of many economically important dicots. The genetics of pathogenesis in V. dahliae has been extensively studied. Spt-Ada-Gcn5 acetyltransferase complex (SAGA) is an ATP-independent multifunctional chromatin remodeling complex that contributes to diverse transcriptional regulatory functions. As members of the core module in the SAGA complex in Saccharomyces cerevisiae, Ada1, together with Spt7 and Spt20, play an important role in maintaining the integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…The cotton 18S gene and N. benthamiana EF-1 α were used as the endogenous plant reference gene. The primers are listed in Table 1 ( Geng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The cotton 18S gene and N. benthamiana EF-1 α were used as the endogenous plant reference gene. The primers are listed in Table 1 ( Geng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we began to investigate the core module in C. neoformans, starting with Hfi1. The understanding of this protein in fungi is extremely limited; the S. cerevisiae hfi1∆ mutant exhibits sensitivity to caffeine, a requirement for inositol [35], while in the soil-borne plant pathogen, Verticillium dahliae, the mutant has defects in multiple phenotypes contributing to virulence [69]. In this study, we also observed a pleiotropic phenotype for the hfi1∆ mutant, this time in the top-ranked Critical Priority Group species from the World Health Organization fungal priority pathogens list.…”
Section: Discussionmentioning
confidence: 53%
“…Conidial germination is one of the factors to affect the development and prevalence of plant pathogens [ 32 ]. Hence, conidia production ability was determined to assess the inhibitory efficacy of KRS010 against V. dahliae .…”
Section: Resultsmentioning
confidence: 99%